SYNTHESIS OF SUBMICRON SIZE TIN DIOXIDE PARTICLES BY OXIDATIVE DISSOLUTION AND PRECIPITATION METHOD IN NITRIC ACID SOLUTION - Irawan Chiong, Daniel
Indonesia is currently the third largest producer of tin metal in the world. PT Timah. has produced several tin processing and refining products such as tin ingots, tin solder, tin granules, and tin chemicals. Demand from the global market and technological advances will open opportunities for the development of tin derivative products such as tin dioxide powder (SnO2) which has physical and chemical properties that can be applied to the semiconductor industry, catalysts, energy storage devices, and gas sensors. Pure SnO2 particles can be synthesized by precipitation methods, one of which is by oxidative dissolution of Sn powder and precipitation of SnO2 in nitric acid solution. This study was conducted to study the effect of HNO3 concentration, leaching temperature, process time, and solid/liquid ratio (S/L) on the size of the SnO2 particles produced and to determine the optimum conditions that produce the smallest particle size, and to study the morphology and purity of SnO2 particle products produced by the synthesis method in HNO3 media. The SnO2 powder synthesis experiment was conducted in 2 (two) stages. The Stage I experiment was designed using the Taguchi Method and was conducted to determine the optimum conditions of the experiment that produced SnO2 particles with the smallest average size. The concentration of nitric acid (HNO3) was varied at 2, 3, and 4 M, the solution temperature was varied at 30°C, 50°C, and 70°C, the solid-liquid ratio (g/mL) was varied at 1/100, 1.5/100, and 2/100 g/mL, while the synthesis time was varied at 2, 4, and 6 hours. The Stage II experiment was conducted by further varying the HNO3 concentration, time, and S/L ratio at 2, 3, and 4 M, 1, 1.5, and 2 hours, and 0.25/100, 0.5/100 and 1/100 g/mL, respectively. The resulting products were measured by particle size analysis (PSA) to determine the average particle size and analyzed by SEM-EDS to determine the morphology and impurity metal content in SnO2 particles. The results of the Phase I Experiment showed that the process temperature had the greatest effect on particle size with a contribution of 50% based on the ANOVA results. The optimum condition obtained based on the analysis of the largest smaller the better S/N ratio in the Taguchi Method was at a concentration of 2M HNO3, a temperature of 30°C, S/L = 1/100 g/mL, and synthesis duration of 2 hours. The optimum condition obtained from further experiments in Phase II was at a concentration of HNO3 = 3M, temperature = 30°C, S/L ratio = 0.25:100 g/mL, and a synthesis time = 2 hours. The particles produced under these conditions had an average PSA size of 158.83 nm. SEM-EDS analysis showed agglomerated particles with globular-clumped-florets morphology and had a calculated purity of 99.76%.